1942
DOI: 10.1002/cber.19420750614
|View full text |Cite
|
Sign up to set email alerts
|

4.4′‐Diamino‐benzophenon und andere schwefelfreie Verbindungen mit Sulfonamidwirkung

Abstract: Kr. 6,'19421 K u h n . N o l l e r . Wendt. B e i n e r t . 711 Richard Kuhn, E r n s t F r i e d r i c h M o l l e r , Gerhard Wendt und H e l m u t h B e i n e r t : 4.4'-Diamino -bemophenon und andere schwefelfreie Verbindungen mit Sulfonamidwirkung.us (1. Kaiser-\Villiel!tl-Institut fur JIedizin. Forschung, Heidelberg, Institut fur C1ieniie.j

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

1942
1942
1989
1989

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…From this it would appear that the NH2E 7 nucleus may be basic for true SA-like activity after all (84). Kuhn et al (133), however, observed PABA antagonism of 4,4'diamino-benzophenone, 4,4'-diamino-diphenylsulfone, phosphanilic acid and carbopyridin; this indicates that, using PABA reversal as a criterion, the sulfur is not indispensable for true SA-like action.…”
Section: 34mentioning
confidence: 95%
“…From this it would appear that the NH2E 7 nucleus may be basic for true SA-like activity after all (84). Kuhn et al (133), however, observed PABA antagonism of 4,4'diamino-benzophenone, 4,4'-diamino-diphenylsulfone, phosphanilic acid and carbopyridin; this indicates that, using PABA reversal as a criterion, the sulfur is not indispensable for true SA-like action.…”
Section: 34mentioning
confidence: 95%
“…Several derivatives could, to some extent, replace PABA, while p-aminobenzamide was either a growth factor or an inhibitor depending on the concentration. The corresponding thioamide was a growth inhibitor, but Kuhn et al (207) concluded that the thioamide competed with'the organisms for iron, since its bacteriostatic effect could be reversed by iron salts but not by PABA. The corresponding thioamide was a growth inhibitor, but Kuhn et al (207) concluded that the thioamide competed with'the organisms for iron, since its bacteriostatic effect could be reversed by iron salts but not by PABA.…”
Section: Other Paba Antagonistsmentioning
confidence: 99%
“…However, the activity dropped off rapidly with time, and Kuhn et al(207) suggested that a "self-inhibition" caused by the formation of PABA might occur. I1 and IV) produces a thirtyfold increase in effectiveness.…”
mentioning
confidence: 99%
“…The antimicrobial activity of PA, as that of the sulfonamides, has been reported to be antagonized by pABA in intact cells (4)(5)(6). The antimicrobial spectrum of PA resembled that of the sulfonamide sulfamethoxazole, but PA had significantly greater activity against Pseudomonas aeruginosa (6).…”
mentioning
confidence: 99%